Pengaruh Konten Edukatif, Influencer Marketing, Dan Program Promosi Digital Terhadap Keputusan Pembelian Produk Skintific Melalui Brand Trust Sebagai Variabel Mediasi - Khilofah, Nurul; Nila Sari, Vivi; Mulyadi, Olandari (Jurnal Ekonomi dan Bisnis Digital, 2026)
The purpose of this study is to analyze the influence of educational content, influencer marketing, and digital promotional programs on purchasing decisions for scientific products through brand trust as a mediating variable. This research is quantitative. Data collection techniques used questionnaires and observations, with a sample of 100 respondents. The data analysis technique used in this study was the SmartPLS 3 program, conducting validity tests, reliability tests, and hypothesis tests.. The results of the study indicate that 1. Educational content has a significant effect on brand trust. 2. Influencer marketing has a significant effect on brand trust. 3. Digital promotion programs have an insignificant effect on brand trust. 4. Educational content has a significant effect on purchasing decisions. 5. Influencer marketing has an insignificant effect on purchasing decisions. 6. Digital promotion programs have an insignificant effect on purchasing decisions. 7. Brand trust has a significant effect on purchasing decisions. 8. Brand trust mediates educational content on purchasing decisions. 9. Brand trust mediates influencer marketing on purchasing decisions. 10. Brand trust does not mediate digital promotion programs on purchasing decisions. Based on the results of this study, it is expected that Skinific products can further improve purchasing decisions by enhancing educational content, influencer marketing, digital promotion programs, and brand trust through each indicator.